2023
DOI: 10.1039/d2ta06801j
|View full text |Cite
|
Sign up to set email alerts
|

Boosting electrocatalytic water oxidation of NiFe layered double hydroxide via the synergy of 3d–4f electron interaction and citrate intercalation

Abstract: Rational morphology design and electronic structure modulation can facilely boost the oxygen evolution reaction (OER) of NiFe layered double hydroxides (LDHs). Herein, hierarchical trimetallic NiFeCe-LDH intercalated with citrate anions was...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…S7a †). 67,68 Cell performance tests were conducted at a temperature of 80 °C (55 °C) and a ow rate of 30 wt% (1 M) KOH solution equal to 200 ccm (300 ccm).…”
Section: Water-splitting Cell Performances Of Electrocatalystsmentioning
confidence: 99%
“…S7a †). 67,68 Cell performance tests were conducted at a temperature of 80 °C (55 °C) and a ow rate of 30 wt% (1 M) KOH solution equal to 200 ccm (300 ccm).…”
Section: Water-splitting Cell Performances Of Electrocatalystsmentioning
confidence: 99%
“…In order to further enhance the catalytic performance of electrode materials, especially for electrical conductivity and stability, in this work, we introduce Ce element to construct 3d–4f trimetallic MOF-74, named (FeMnCe)-MOF-74. As reported in previous literature, 51–55 (1) the unique 4f orbitals of rare earth (RE) elements can overlap and hybridize with other orbitals, thereby adjusting the electronic structure of the target material; (2) the coupling between the d and f orbitals can build electronic ladders, which is conducive to charge transfer; (3) the materials constructed by 3d transition-metal atoms and 4f rare earth metals usually exhibit oxygen vacancy-enriched structural characteristics due to different atomic radii and coordination configurations, which lead to lattice distortion. Therefore, a 3d–4f mixed metal strategy is a very effective method to improve the electrocatalytic performance of MOF-based catalysts.…”
Section: Introductionmentioning
confidence: 98%
“…[22][23][24][25] For example, Wan et al showed that doping Ce into the NiFe LDH lattice greatly changed the electronic structure, thus optimizing the adsorption/desorption performance of the reactants and intermediates. 26 Zhao et al, through Mo doping, could effectively improve the lattice oxygen activity in NiFe (hydroxyl) hydroxide, thus significantly enhancing the intrinsic activity of the OER. 27 Vanadium is a transition metal abundant on Earth and is considered a potential dopant candidate.…”
Section: Introductionmentioning
confidence: 99%